CHARACTERIZATION OF MELOXICAM LOADED GEL-EMULSION - Drakalska Sersemova, Elena; Cvetkovski, Aleksandar; Angelovska, Bistra; Miceva, Dijana; Makraduli, Liljana (Archives of Pharmacy, 2023)
Meloxicam is one of the most potent non-steroidal anti-inflammatory drugs, generally indicated for treatment of rheumatoid arthritis, osteoarthritis, and juvenile arthritis and commercially available in form of tablets and solution for IV use with recommended daily dose 7.5-15 mg. Unfortunately, long-term administration usually in higher doses is associated with increased risk of gastro-intestinal bleeding, cardiac arrest, and stroke. An alternative approach to overcome these limitations is the design of topical forms. The aim of this study is characterization and evaluation of gel-emulsion with meloxicam. The present study is focused on elaboration of gel-emulsion composed of TEGO Carbomer 134 as gelling agent, propylene glycol as solubilizer and humectant, Tween 60 and Span 60 as emulsifiers, liquid paraffin as vehicle of oil phase from gel-emulsion, triethanolamine as pH adjuster and menthol as rubefacient whereby meloxicam is incorporated as free drug in oil phase. Prepared gel-emulsion was characterized by meloxicam content, pH, spreadability, viscosity and evaluation of microbiological quality. Obtained results showed homogenous, easy spreadable, translucent gel-emulsion. Upon visual examination, no phase separation was observed. The percentage of drug content in gel-emulsion was 103%, spreadability was 9.2 cm and viscosity was 25 500 CP. Measured pH was 6.45 which is suitable for dermal application without risk of irritation. Additionally, absence of the specific microorganisms Escherichia coli, Salmonella, Pseudomonas aeruginosa, Staphylococcus aureus, Clostridia and Candida albicans was determined. The tested formulation was physicochemically stable and of adequate microbiological quality after three months of preparation, however, further research is needed to determine the safety of the developed gel-emulsion.